CARDIOPRODUCTIVE EFFECTS OF EXXENATE AMID AND VILDAGLIPTIN INCRETIN MIMETICS IN DOXYRUBRICINE CARDIOMYOPATHY MODELING - A. P. TARASOVА; A. V. KHAVANSKY; A. S. TIMOKHINA; A. P. DOVGAN; D. A. KOSTINA; L. N. SERNOV (Кубанский научный медицинский вестник)
Aim. To study the cardioprotective effects of exenatide and vildagliptin on the doxorubicin model of cardiomyopathy.Material and methods. In the experiments at the isolated the Langendorff heart of the rat, the cardioprotective effect of exenatide (10 μg/kg/day) (Baeta®, Eli Lilly and Company, USA) and vildagliptin (0.2 mg/kg/day) (Galvus®, Novartis, Switzerland), on the contractile function of an isolated heart that underwent anterior doxorubicin (20 mg/kg, intraperitoneally for 48 hours) pathology was evaluated. Cardioprotective effect was assessed by the results of a functional test with highfrequency stimulation (480 bpm) under conditions of hypercalcium (5 mmol) perfusion.Results. The results show that the exenatide (10 μg/kg/day) and vildagliptin (0.2 mg/kg/day) incretin mimetics show a cardioprotective effect on the doxyrubicin pathology model, which is expressed in a decrease in the coefficient of diastolic dysfunction (StTTI), respectively, to 5.3±0.1 cu and 6.5±0.2 cu compared with the control group 8.3±0.1 cu.Conclusion. An assumption is made about the way of realization of the cardioprotective effect of incretin mimetics by increasing the expression of gem-oxygenase-1 (HO-1). This prevents the heme-catalyzed formation of highly active hydroxyl radicals from hydrogen peroxide. Induction of heme oxygenase-1 is accompanied by an increase in ferritin activity, which has an antiapoptotic effect due to the fact that ferritin binds excess free iron in cells subjected to oxidative stress.